Customer Affecting-Satisfaction Factors in Electronic Banking Systems: Three Significantly Selected Research Perspectives - Rahmah Mohammed Salih Saeed Al Ali Khan (Iraqi Journal of Science, 2021)
The future of the highly competitive global banking is electronic banking via internet. This trend of electronic delivery of banking products and services is necessitated by the customers’ demanding more Internet-customized daily transaction. Hence, customer affecting-satisfaction factors need to be thoroughly investigated in order to deliver efficient electronic banking. Consequently, this paper reviewed three approaches to reach the most influential customer affecting-satisfaction factors. These customer affecting-satisfaction approaches are prioritizing based on cause and effect relationships, understanding with the use of a questionnaire survey and better communicating using e-mail and social media. The pool of customer affecting-satisfaction factors is quality of services, reliability, privacy and confidentiality, site aesthetics, ease of use, convenience, communication speed (via e-mail and social media), fulfillment, responsiveness/contact, efficient and other future emerging factors. The most important factor results from first, second and third approach is the ease of use, friendly website navigation, and communication speed respectively.